Menyoal Jenis Kelamin Allah dalam Perspektif Teologi Feminis: Menuju Teologi yang Lebih Berkeadilan terhadap Perempuan - Christian Siregar (Humaniora, 2015)
Gender inequality is often regarded as a divine creation (everything comes from God, or commonly known, already by nature). This is where the Christian theology actually gets a touchstone. Because theology should be a critical reflection religion on factual issues faced by the public, so that it should talk not only about the concept of invicible God, but also that metaphysical translated into social issues—particularly women's issues. At that point, theology of woman is a theology which explores the feminine aspects of God for the sake of gender equality. This study attempted to trace the theological dimensions of women as well as exploring the feminine attributes of God so that gender equality can be realized, or at least theology does not fold its eyes, or theology is to be fair to the existence of woman. This research is a literature study using representative literature data and relevant to the object of research. Research used philosophical approach with descriptive-analytic-critical method by doing interpretation, extrapolation, the meaning of the data in reaching a conclusion. Results showed that the lowering of woman feminine quality is equivalent to neglect the feminine quality of God. On that basis, gender discrimination actually has no theological justification, but is a denial of the reality of God as a whole. The reason is gender relations are impressively has been represented by God.